Arboreal Burials in Nicrophorus spp. (Coleoptera: Silphidae) - Amanda J. Lowe; Randolph F. Lauff (Psyche: A Journal of Entomology)
Nicrophorus beetles are well known for interring small vertebrates below ground for the purpose of rearing their young. However, the arboreal use of carrion has not been previously investigated. Nest boxes were suspended in the canopy of two forest habitats in Nova Scotia, Canada, to determine if this microhabitat fostered the same behaviour. Although four species of Nicrophorus as well as Oiceoptoma noveboracense (Forster) were recorded in association with carrion, arboreal reproduction was recorded exclusively and for the first time in N. tomentosus Weber and N. defodiens Mannerheim. Both N. sayi Laporte and N. pustulatus Herschel were associated with the arboreal carrion but did not reproduce on it during these experiments.